2023
DOI: 10.1051/0004-6361/202245449
|View full text |Cite
|
Sign up to set email alerts
|

Globular clusters in the Galactic center region: Expected behavior within the infall and merger scenario

Abstract: In this work, we reexamine the infall and merger scenario of massive clusters in the Milky Way’s potential well as a plausible Milky Way formation mechanism. We aim to understand how the stars of the merging clusters are redistributed during and after the merger process. We used, for the first time, high-resolution simulations with concentrated in the 300 pc around the Galactic center. We adopted simulations developed in the framework of the Modelling the Evolution of Galactic Nuclei (MEGaN) project. We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…A sig-nificant number of these dynamical processes are stronger in the deep potential well of the inner Galaxy. Numerical simulations have revealed that the supermassive black hole Sagittarius A* (Ghez et al 2008;Genzel et al 2010) can very efficiently grind clusters, and is a place where globular clusters could be rapidly demolished (Arca-Sedda & Capuzzo-Dolcetta 2017; Navarro et al 2023). In order to address the process of globular-cluster disruption, it is crucial to understand not only clusters that have been destroyed but also surviving globular clusters.…”
Section: Introductionmentioning
confidence: 99%
“…A sig-nificant number of these dynamical processes are stronger in the deep potential well of the inner Galaxy. Numerical simulations have revealed that the supermassive black hole Sagittarius A* (Ghez et al 2008;Genzel et al 2010) can very efficiently grind clusters, and is a place where globular clusters could be rapidly demolished (Arca-Sedda & Capuzzo-Dolcetta 2017; Navarro et al 2023). In order to address the process of globular-cluster disruption, it is crucial to understand not only clusters that have been destroyed but also surviving globular clusters.…”
Section: Introductionmentioning
confidence: 99%